Arrangements for special and intensive care of the newborn. Issue 6094 (22nd October 1977) - Alberman, E; Collingwood, J; Pharoah, P O; Vaizey, J; Oppé, T E
Abstract : All the special care baby units in three Thames health regions completed a one-day census on the number of infants in the unit, staffing, and facilities. The results were assessed in the light of the recommendations of an expert group set up by the Department of Health and Social Security. Although the provision of cots (6.1-6.9 per 1000 live births) was more generous than the estimated need and the occupancy rate (59–63%) lower than suggested, some units did not have adequate trained nursing cover at night, some did not have resident paediatricians, and some lacked essential equipment. Some small units, on the other hand, had very expensive equipment that was probably underused. Relating this provision to the regional statistics on babies needing special care showed that there was room for the rationalisation of facilities for their care. Factors that should be considered in planning such care include the size of the child-bearing population, the percentage of infants of low birth weights, and the proximity of specialist paediatric and maternity units and pathology facilities. It is also essential to monitor the effectiveness of the care by assessing the outcome in babies admitted to special units, especially those of low birth weight.